Human Trafficking as a Threat to Personal Security - Pajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The subject of this article is human trafficking in the context of endangering personal security, with an individual as a reference object in need of protection. The author employs a literature review as the primary research method. The aim is to synthesize available scholarly literature and gain insights into existing theoretical generalizations and findings of empirical research examining human trafficking as a threat to personal security. Given the multidisciplinary nature of the subject, the analysis encompasses scholarly articles from various fields, particularly security studies and migration studies. The findings reveal that victims experience physical, psychological and sexual violence throughout different stages of the trafficking process, extending beyond the exploitation phase, as commonly acknowledged. The primary objective of employing various forms of violence is to maintain victims in a submissive and slave-like position, reinforcing the belief that escape is impossible. It is worth noting that researchers primarily focus on sexual exploitation, resulting in a larger body of work addressing women and girls as victims of human trafficking. Future research should aim to explore further other less visible forms of human trafficking, which may have equally severe implications for personal security. Additionally, the ongoing challenge of identifying these victims perpetuates the vicious circle of victimization. For holistic insights, it is necessary to examine this issue from a broader perspective on human security.